Model Pembelajaran Cooperative Learning Tipe Jigsaw Pada Mata Kuliah Manajemen Pemasaran Prodi Manajemen FEB Universitas Jambi - Hasbullah, Husni; Bhayangkari, Sylvia Kartika Wulah (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2023)
In participating in learning, students' abilities vary, including in the Marketing Management Course in the Management Study Program, even though the students are in the same class, the learning methods are the same and the material presented is also the same. It is often found that the ability of one student is far more than the class average and other students, while some are far below the class average. This can be seen when learning using the discussion/question and answer method is often dominated by intelligent students so that students with low abilities do not provide opportunities. Apart from that, when this conventional pattern is applied, student absorption in Marketing Management courses is low, which is also caused by their low learning motivation. In general, they think that this course is not important so they are lazy to take this course. Some students also think that this course does not make a contribution to their knowledge. In this case, one effort to create an effective learning process is through Jigsaw Type Cooperative Learning because it is very suitable for subjects such as social science lessons, literature, some scientific science lessons and other fields where the learning objective is more about mastering concepts. rather than mastery of abilities. Jigsaw type cooperative learning method, students work together to achieve the same goal. Each group member is required to be responsible for their learning outcomes, because the success of the group is based on the contribution of each group member. The results of the research concluded that the Jigsaw technique cooperative learning method had a positive influence on learning outcomes (cognitive aspects). This can be explained that the activities in cooperative learning using the jigsaw technique are different from the group discussion method. It can be explained that in the jigsaw cooperative learning method, students work together to achieve the same goal. Each group member is required to be responsible for their learning outcomes, because the success of the group is based on the contribution of each group member. In this way, each student is motivated to learn, encouraging each other and helping each other among group members to learn optimally